Evaluation of Electrochemical Methods for Determination of the Seebeck Coefficient of Redox Electrolytes. (1st December 2015) - Koerver, Raimund; MacFarlane, Douglas R.; Pringle, Jennifer M.
Graphical abstract: Highlights: Three different techniques for analyzing the temperature dependence of the electrochemical potential of a cobalt redox couple are compared. This redox couple is of interest for thermal energy harvesting applications. Cyclic voltammetry can be used to determine this temperature dependence, and thus the Seebeck coefficient, even with only one half of the redox couple present. Abstract: Recent advances in thermoelectrochemical cells, which are being developed for harvesting low grade waste heat, have shown the promise of cobalt bipyridyl salts as the active redox couple. The Seebeck coefficient, Se, of a redox couple determines the open circuit voltage achievable, for a given temperature gradient, across the thermoelectrochemical cell. Thus, the accurate determination of this thermodynamic parameter is key to the development and study of new redox electrolytes. Further, techniques for accurate determination of Se using only one half of the redox couple reduces the synthetic requirements. Here, we compare three different experimental techniques for measuring Se of a cobalt tris(bipyridyl) redox couple in ionic liquid electrolytes. The use of temperature dependent cyclic voltammetry (CV) in isothermal and non-isothermal cells was investigated in depth, and the Se values compared to those from thermo-electromotive force measurements. Within experimental error, the Se values derived from CV methods were found to be in accordance with those obtained from electromotive force (emf) measurements. The applicability of cyclic voltammetry techniques for determining Se when employing only one part of the redox couple was demonstrated.